Relationship Between Intensity of Listening to The Song Diri by Tulus and Self-Acceptance in The Solo Tulus Friends Community - Tsaqifa, Firratu; Fitriani, Afia (Jurnal Seni Musik, 2023)
Self-acceptance is an essential component of psychological well-being, and music or songs have their potential to contribute to mental health and well-being. This research aims to determine the influence of the intensity of listening to the song Diri by Tulus on self-acceptance in the Teman Tulus Solo Community. The research method used is quantitative with person-product moment correlation. The research population is members of the Teman Tulus Solo Community who follow the official Instagram account @temantulussolo and live in Solo Raya (Surakarta, Boyolali, Sukoharjo, Karanganyar, Wonogiri, Sragen, and Klaten). The sampling technique uses snowball sampling. The total sample size was 102 respondents, consisting of 89 women and 13 men. The instruments in this research were the intensity scale for listening to self-songs (α=0.812) and the Berger Self-Acceptance Scale (α=0.844), distributed online in the form of a Google form to respondents. Based on the correlation test results, there is a significant relationship between the intensity of listening to the song Diri and self-acceptance (p=0.035; r=0.209).